(untitled) (INCH : Journal of Infant and Child Healthcare, 2023)
Management of fishery waste that has not been optimally implemented, such as catfish bones in the processed food industry will have an adverse impact on the environment. Utilization of waste can be done by turning it into bone meal which can be used as an addition to nutritional value in complementary foods such as biscuits. This processed food is expected to help the government in tackling the ongoing stunting problem. Before being distributed, biscuits should meet the requirements for macro-nutritional value that have been set. The purpose of this study was to analyze the levels of macro content in biscuits that had been fortified with catfish bone meal, namely carbohydrates, fats and proteins. This research uses descriptive data analysis method. The treatment in this study was to formulate biscuits with the addition of catfish bone flour 0(F0), 25% (F1) and 50%(F2). Based on the tests that have been carried out on the content of carbohydrates, fats and proteins meet the requirements of biscuits based on SNI 2973-2011